Pengaruh Lingkungan Kerja dan Motivasi terhadap Disiplin Serta Dampaknya pada Kinerja Pegawai Aparatur Sipil Negara Dinas Perhubungan Provinsi Jambi - Candra Edi; Arna Suryani; Fakhrul Rozi Yamali; Fakhrul Rozi Yamali (J-MAS (Jurnal Manajemen dan Sains), 2023)
The purpose of this study is to describe the work environment, work motivation, work discipline and employee performance at the Jambi Province Transportation Service and to analyze the effect of the work environment and work motivation partially and simultaneously directly and indirectly on work discipline and employee performance, as well as to analyze work discipline on employee performance. To answer the research objectives, this research is supported by theoretical studies related to research variables, namely work environment, work motivation, work discipline, and performance. In addition, the authors also look for relevant previous research in the form of previous articles/journals and theses to support this research. The population in this study were employees of the Jambi Province Transportation Service, totaling 61 employees with conditions in 2022. The data analysis technique used in this study was through path analysis followed by hypothesis testing through the F test (Simultaneous) and t test (Partial). From the path analysis test carried out, it was found that the work environment and work motivation have an influence on work discipline and employee performance, both directly and indirectly. This explains that if the organization has a good work environment and the better the work environment then this will further improve employee discipline towards the organization and provide maximum work results.